A facile fabrication of 1D/2D nanohybrids composed of NiCo-hydroxide nanowires and reduced graphene oxide for high-performance asymmetric supercapacitors. Issue 1 (6th November 2019) - Zhang, Xu; Fan, Qiuyu; Liu, Siyu; Qu, Ning; Yang, He; Wang, Man; Yang, Juan
Abstract : 1D/2D nanohybrids composed of NiCo-hydroxide nanowires and graphene have been successfully fabricated by a simple method. Abstract : A novel 1D/2D hybrid design is reported for synthesizing a high performance NiCo-hydroxide nanowires/reduced graphene oxide (NiCo-NWs/G) composite. The oxygen-containing groups on the graphene oxide surface can act as anchoring sites for uniformly adsorbing the metal seeds, leading to the dispersed formation of thin NiCo-NWs on the graphene surface. The existence of graphene in NiCo-NWs/G can provide a conductive network to boost the faradaic reactions. In addition, the bimetallic NiCo-NWs possess rich redox reaction sites and the thin nanowire structure ensures that electrons can move rapidly from the reaction sites to the current collectors. Owing to the synergic effects of 1D NiCo-NWs and 2D graphene, the developed NiCo-NWs/G electrode exhibits an excellent performance of 1449 F g −1 at a current density of 1 A g −1, a high rate capability of 61% at 20 A g −1, and a good cycling stability in 6 M KOH electrolyte. Moreover, the asymmetric supercapacitor with NiCo-NWs/G as a positive electrode and active carbon as a negative electrode delivers a high energy density of 42.1 W h kg −1 at a power density of 0.8 kW kg −1 . This work may pave a promising new way for the development of 1D/2D composites based on pseudocapacitive hydroxides and carbon materials for high-performance asymmetric supercapacitors.